2010
DOI: 10.1590/s0100-736x2010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss on the cardiac parameters of obese dogs

Abstract: Obesity is one of the most frequent nutritional problems in companion animals and can lead to severe health problems in dogs and cats, such as cardiovascular diseases. This research aimed to evaluate the structural and functional cardiac changes after weight loss in obese dogs. Eighteen obese healthy dogs were assigned into three different groups, according with their initial body weight: Group I (dogs up to 15 kg), Group II (dogs weighing between 15.1 and 30 kg), and Group III (dogs weighing over 30 kg). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
4
16
0
3
Order By: Relevance
“…Studies in humans and animals reveal that body weight and obesity can influence ECG tracings (Alpert et al 2001, Talavera et al 2008, Neto et al 2010). In our study, the similarities found while comparing body weight/size of the animals can be attributed to the fact that all animals were standardized and healthy, with no signs of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and animals reveal that body weight and obesity can influence ECG tracings (Alpert et al 2001, Talavera et al 2008, Neto et al 2010). In our study, the similarities found while comparing body weight/size of the animals can be attributed to the fact that all animals were standardized and healthy, with no signs of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…They are also more sensitive to cardioactive glycosides than rats and mice, therefore indicated for the investigation of these inotropic agents (Akera et al 1979). Animals ECG patterns can be different accordingly to the body weight and fat deposit, causing cardiac changes that can be seen in the ECG (Neto et al 2010). Therefore the purpose of this study is to evaluate healthy conscious guinea-pig as a model for electrophysiology assessment and to describe normal ECG patterns in controlled laboratory environment using computerized electrocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in information technology, the computerized electrocardiogram has been used in human medicine as an auxiliary diagnostic method and is currently used increasingly in veterinary medicine (Tilley 1981, Andrade et al 2004, Aptekmann et al 2010, Neto et al 2010, Gava et al 2011. According to Tilley (1992), in veterinary medicine, the computerized ECG improved the quality of emergency electrocardiogram services and other advantages including a decrease in the time needed to carry out the exam.…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, considerou-se um bom método de avaliação corporal para classificação da obesidade nos animais do presente estudo, uma vez que foi realizado em um único momento em dois grupos distintos, sem avaliar a perda de peso no mesmo animal. Todos os valores da pressão arterial sistólica encontram-se dentro do intervalo de referência para a espécie e foram semelhantes aos descritos previamente por outros autores, situando-se entre 110mmHg a 160mmHg (Stepien et al 2003, Brown et al 2007, Pereira Neto et al 2010. Ao se comparar os valores obtidos pelos dois métodos indiretos de mensuração da PAS, encontrou-se valores inferiores significativos pelo método oscilométrico em cães obesos.…”
Section: Discussionunclassified